1987
DOI: 10.1128/aem.53.9.1987-1995.1987
|View full text |Cite
|
Sign up to set email alerts
|

Mixed fungal populations and lignocellulosic tissue degradation in the bovine rumen

Abstract: Anaerobic fungi in ruminal fluid from cows eating Bermuda grass hay plus a grain and minerals supplement were evaluated for diversity in sporangial morphotypes and colony growth patterns and for the degradation of various lignocelluloses. In selective cultures containing streptomycin and penicillin, an active population of ruminal fungi colonized leaf blades and degraded fiber at rates and extents almost equal to that of the total ruminal population. Three major sporangial morphotypes were consistently observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 33 publications
2
37
0
1
Order By: Relevance
“…Under similar conditions the photodimer was non-toxic ( Table 2 ) . The data confirm the extremely toxic nature of p-coumaric acid to rumen microorganisms noted in earlier work (Jung and Sahlu 1986;Akin and Rigsby 1987), and establish the highly toxic nature of the esters. It is also of interest to note that, as indicated in earlier studies (Akin and Rigsby 1987), the activity of the fungi was enhanced when bacteria were removed ( Table 2).…”
Section: Toxic Effects Of Phenolic Compounds On Fibre Degradation By supporting
confidence: 87%
See 2 more Smart Citations
“…Under similar conditions the photodimer was non-toxic ( Table 2 ) . The data confirm the extremely toxic nature of p-coumaric acid to rumen microorganisms noted in earlier work (Jung and Sahlu 1986;Akin and Rigsby 1987), and establish the highly toxic nature of the esters. It is also of interest to note that, as indicated in earlier studies (Akin and Rigsby 1987), the activity of the fungi was enhanced when bacteria were removed ( Table 2).…”
Section: Toxic Effects Of Phenolic Compounds On Fibre Degradation By supporting
confidence: 87%
“…The data confirm the extremely toxic nature of p-coumaric acid to rumen microorganisms noted in earlier work (Jung and Sahlu 1986;Akin and Rigsby 1987), and establish the highly toxic nature of the esters. It is also of interest to note that, as indicated in earlier studies (Akin and Rigsby 1987), the activity of the fungi was enhanced when bacteria were removed ( Table 2). The addition of the photodimer did not lead to a significant difference ( P < 0.05) from the control in any test (Tables 1 and 2), suggesting that the compound was non-toxic or the level of toxicity was too low to be detected.…”
Section: Toxic Effects Of Phenolic Compounds On Fibre Degradation By supporting
confidence: 87%
See 1 more Smart Citation
“…The earlier reports in literature indicate that rumen fungi are more resistant to phenolic monomers as compared with other rumen microbes (Akin and Rigsby 1987). Borneman et al (1986) observed varied effects of phenolic monomers on bacteria (inhibitory or stimulatory), depending on the compound and the microbial species.…”
Section: Tolerance To Phenolic Monomersmentioning
confidence: 92%
“…Rumen fungi produce all enzymes necessary both for depolymerization of cellulose and hemicellulose and hydrolysis of free oligosaccharides (Akin and Rigsby 1987;Mountfort 1987). Up to now no described isolate was able to grow on pectin alone (Orpin and Joblin 1987).…”
Section: Introductionmentioning
confidence: 99%